Therapeutic Plasma Exchange in Pediatric Kidney Disease: 23-year Experience at the Severance Children's Hospital in Korea - Sun Mi Her; Keum Hwa Lee; Ji Hong Kim; Jae Seung Lee; Pyung Kil Kim; Jae Il Shin (Korean Society of Pediatric Nephrology, 2017)
Purpose The American Society for Apheresis provides clinical guidelines for therapeutic apheresis in adults, but there are no guidelines for children. This study aimed to analyze the effect of therapeutic plasma exchange (TPE) in pediatric patients with various kidney diseases in Korea. Methods We retrospectively reviewed the data of 16 children (up to 18 years of age) who were admitted to Severance Children's Hospital with refractory kidney disease. All patients received TPE between 1994 and 2016. Clinical and laboratory characteristics such as age, weight, sex, change in blood urea nitrogen (BUN), and creatinine level before and after TPE, and complications after TPE were analyzed. Results The mean age and weight of the 16 patients at the time of TPE was 11.3±4.0 years and 34.6±17.5 kg, respectively. The BUN level was 35.4 mg/dL before TPE and significantly decreased to 21.5 mg/dL (P=0.025) at 1 week and 20.5 mg/dL (P=0.01) at 1 month after TPE. The creatinine level significantly decreased from 1.20 mg/dL before TPE to 0.90 mg/dL (P=0.02) at 1 week after TPE. Four complications (hypovolemia, anemia, hypocalcemia, and thrombocytopenia) were reported, but were not fatal. Conclusion Our findings suggest that TPE is an effective therapeutic modality in children with refractory kidney disease and can be indicated for the treatment of various kidney diseases.